Case Study Of Hotel Menara Peninsula Jakarta - Oktadiana, Hera (2006)
This case study focuses on the hotel industry, and is divided into two parts: the case writing and the case analysis. Based on the strategic management input, the writer would like to describe the strategic formulation, strategic implementation and the evaluation and control process in the industry, represented by a leading four-star hotel in Jakarta, the Hotel Menara Peninsula.